H2S, anoxic, PLTA, Sistem Pembuangan Lokal - Fadian, Yusuf
Jatiluhur reservoir had been found in an anoxic condition which increase the organic content of the reservoir and produce dissolved H2S gas. Water from Jatiluhur reservoir is harness by Jatiluhur Hydroelectric Power plant, resulting an emission of H2S gas inside the powerhouse and control room. Implementation of Local Exhaust Ventilation System can be done to control H2S emission in workplace environment. Local exhaust ventilation system is composed of four components: hood, ducting system, air cleaning device, and fan. The purpose of this design is to propose an alternative design of local exhaust ventilation components as a control measure for H2S emission inside the powerhouse and control room of Jatiluhur hydroelectric power plant. There are two design alternative; design based on the concentration gradient of H2S and design based on temperature gradient; in which out of the two alternatives one will be chosen according to each alternative’s pressure loss. H2S concentration gradient was obtained by inputing nine concentration points as a contour map on surfer program. Temperature gradient was obtained by inputing the value of temperature at 22 points as a contour map and vector map then overlay them using surfer program. Design based on concentration gradient is a design that consider the pattern of H2S dispersion while design based on temperature gradient is a design that consider the direction of air flow. The alternative chosen was the design based on temperature gradient which consists of: three hood, seven duct segments, one packed column absorption unit, one fan, and one evase. There are three hoods placement for the chosen alternative. The air velocity at those three points were calculated by theory of gas kinetics. The designed hoods were capturing hood-tapered 60o opening with flowrate of: 3411.3 cfm; 3788 cfm; 6992 cfm. The designed duct segments were stainless steel duct with diameter of: 15”; 16”; 17”; 25”; 28”; 29.5”; 35”. The designed packed column absorber was planned to remove 4,6 ppm of H2S with an efficiency of 99.78%. The chosen fan was a High Capacity Blower with a flowrate capacity of 14122.12 cfm and fan static pressure of 16.24 “water gauge. All the designed components investment costs were then calculated using an interpolation of cost index on year 2015 because the absence of standard unit value for local exhaust ventilation system. The investment costs of the local exhaust system design was: Rp. 80.211.796.733,00. This designed is accompanied by the technical drawings of the chosen design alternative.